Both sides of the couch: a qualitative exploration of the experiences of female healthcare professionals returning to work after treatment for cancer. (25th March 2015) - Mitchell, T.
<x xml:space="preserve">Abstract</x> The aim was to explore the experiences of healthcare professionals (HCPs) who had treatment for cancer and then returned to work. The intention was to identify how HCPs' experiences differed to those of the general public with cancer, and also to explore how HCPs were reintegrated into the workplace following treatment. An interpretive phenomenological approach was employed and conversational interviews were undertaken with 13 women volunteers from a variety of healthcare disciplines including nursing, midwifery, social work, physiotherapy, radiography and general practice. During analysis 59 categories were constructed which were accommodated within 14 themes; six of which are reported here. Participants used knowledge to make sense of their diagnosis, severity and extent of cancer. Several participants covertly accessed their medical records to find out more about their clinical condition. Familiarity with both the environment and oncology personnel resulted in benefits and disadvantage in equal measure. Managers responded to participants' return to work in a variety of ways, and involvement of Occupational Health Departments was inconsistent. Healthcare professionals had distinctly unique experiences because of being patient and provider, and each made personal decisions about sharing their cancer experiences with patients.